Midterm Outcomes of the Endoscopic Endonasal Approach for Treating Tuberculum Sellae Meningiomas: The Impact of Malleable Forceps and Predictors of Surgical Success - Nakase, Kenta; Nagatani, Tetsuya; Ishikawa, Takayuki; Kato, Nobuyasu; Isozawa, Yuichiro; Miyake, Tomiyuki; Sakai, Yosuke; Yokoyama, Hayato; Tsukada, Tetsuya; Sakamoto, Yusuke; Araki, Yoshio; Seki, Yukio (Journal of Neurological Surgery Part B: Skull Base, 2025)
Objective To evaluate the midterm surgical outcomes and factors associated with the extent of resection (EOR), postoperative visual improvement, and risk factors for postoperative cerebrospinal fluid (CSF) leaks in cases of the endoscopic endonasal approach (EEA) for tuberculum sellae meningiomas (TSMs), including cases utilizing the malleable forceps.Design Retrospective clinical study.Setting Single-center tertiary referral hospital.Participants Twenty-two patients who underwent the EEA for TSMs between November 2013 and April 2024.Main Outcome Measures Patient characteristics, intraoperative findings, and postoperative outcomes were evaluated. Predictors of the EOR, postoperative visual improvement, and postoperative CSF leaks were investigated.Results The median age was 58 years, with 77.2% being women. The median follow-up was 70.5 months, and the mean tumor size was 23.5 mm. Gross total resection (GTR) was achieved in 18 patients (81.8%), with no recurrence. Adhesion to the optic nerve was significantly associated with the EOR (p = 0.001). The malleable forceps were used in 14 out of 22 cases, and the GTR rate increased to 92.8% (13 out of 14 cases) with this instrument._Postoperative visual improvement was achieved in 16 of 19 patients (84.2%) and was significantly associated with tumor size (p = 0.02) and the duration of preoperative visual disturbances (p = 0.002). Two patients (9.0%) experienced postoperative CSF leaks, significantly associated with sex (p = 0.04) and Simpson grade (p = 0.032).Conclusion The EEA yielded favorable outcomes and significant postoperative visual improvement for TSMs, supporting early intervention for symptomatic TSMs and radical treatment for GTR. The malleable forceps can enhance the management of complex procedures.
Keywords: tuberculum sellae meningiomas; endoscopic endonasal approach; midterm outcomes; visual impairment; cerebrospinal fluid leaks; malleable forceps